A qualitative study of Irish parents' views on hippotherapy, including its influence on their children's home-based occupations. Issue 1 (16th April 2019) - O'Mahony, Rachel; Connolly, Emma; Hynes, Patrick
Abstract : Purpose: Hippotherapy is an emerging area of paediatric occupational therapy practice in Ireland. It is a treatment strategy used by specially trained occupational therapy practitioners, physical therapists and speech language pathologists as part of the intervention programme to facilitate functional gains. This paper aims to explore parents' perspectives on children's participation in home-based occupations following hippotherapy treatment. Design/methodology/approach: Qualitative, semi-structured interviews were conducted with eight participants. Interviews were audio-recorded and transcribed verbatim. In accordance with thematic analysis, line-by-line coding was completed to identify codes. Codes were organised into categories, which were grouped to develop themes. Findings: Three core themes were identified: lack of knowledge regarding hippotherapy as an occupational therapy intervention; children's increased participation in home-based occupations secondary to improved physical, psychological, communication and social skills; and the unique hippotherapy environment as a motivating factor for children to engage in occupational therapy intervention. Originality/value: Findings from this study support the growing body of evidence that hippotherapy is an effective means of intervention for increasing physical, psychological, social and communication skills. The participants report positive effects following hippotherapy on their children's participation in home-based occupations. It highlights a link between the unique hippotherapy environment and children's increased engagement in occupational therapy. Given that no published hippotherapy-specific literature related to occupational therapy exists in the Irish context, and given that hippotherapy is an emerging area of practice in Ireland, this paper contributes to the knowledge base.